Working with piezo electric disk on "Adam's Dream" - Dahlia Tan, bt. Abdullah. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This report documents the thoughts and works of "Adam's Dream", an experimental electroacoustic composition. It intends to realize a three-year old boy's dream by producing symbolic representations of musical and sonic thoughts. By using piezo electric disk as contact microphone, the recordings ofmicrosound made by ants are taken and used as compositional material together with few insects' sounds. The composition intends to experiment the possible usage ofmicrosound in electroacoustic composition as well as to increase awareness of its existence in our sound ecology.